The first Rhynchomicropteron Annandale, 1912 (Diptera, Phoridae) species from the Palearctic region, with taxonomic and faunistic notes on the fauna of Israel - Lengyel, Gábor Dániel (Zootaxa, 2011)
The first Palearctic species of the genus Rhynchomicropteron Annandale, 1912, R. kuslitzkyi sp. n., is described from Israel. Another five species of Phoridae (Gymnophora arcuata (Meigen, 1830), Metopina heselhausi Schmitz, 1914, Microselia rivierae Schmitz, 1934, Peromitra cephalotes (Schmitz, 1922), Peromitra erythrocera (Meigen, 1830)) are recorded as new to the fauna of Israel. The previously unknown male of Microselia rivierae is described, diagnostic characters of males of the genus Microselia Schmitz, 1934 are discussed.